Education on Secret Marriage Regarding Married Life at the Utsman Bin Affan Islamic Study Group - Saputra, Adzra Emalis; Akhmad Sonny Gunawan; Nurfita Sari; Salsabillah Dani Nur Anisa; Oyoh Bariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This Community Service Activity (PKM) aims to enhance public understanding, particularly among the women of Majelis Ta'lim Utsman Bin Affan, regarding nikah sirri from the perspectives of Islamic law and state law. Many people perceive nikah sirri as purely a religious matter, neglecting its broader implications, particularly on the rights and responsibilities of spouses and children. Through interactive socialization and guidance, participants were provided with detailed explanations and engaged in discussions to facilitate better comprehension of the consequences of nikah sirri. These include its impacts on legal, social, and psychological aspects of family life. The activity showed significant results, with participants demonstrating an 80% improvement in understanding compared to their initial knowledge. This initiative not only increased participants' awareness but also encouraged them to share the knowledge gained with their families and communities. The education provided highlighted the importance of considering religious, legal, and social dimensions in choosing formally registered marriages. The findings indicate that the education offered by Majelis Ta'lim Utsman Bin Affan plays a crucial role in reducing nikah sirri practices and fostering greater public awareness about the necessity of marriage legality. By promoting harmonious family life, this program contributes to building a more legally and socially conscious society.